2017
DOI: 10.5116/ijme.589f.6ef0
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based learning using patient-simulated videos showing daily life for a comprehensive clinical approach

Abstract: ObjectivesWe examined whether problem-based learning tutorials using patient-simulated videos showing daily life are more practical for clinical learning, compared with traditional paper-based problem-based learning, for the consideration rate of psychosocial issues and the recall rate for experienced learning. MethodsTwenty-two groups with 120 fifth-year students were each assigned paper-based problem-based learning and video-based problem-based learning using patient-simulated videos. We compared target achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…The focus group showed that the students with limited clinical experience had difficulty in creating an image of her psychosocial aspects. A lower achievement of imaging was also reported when paper patients were used [16].…”
Section: The Cue Acquisition Stagementioning
confidence: 88%
See 1 more Smart Citation
“…The focus group showed that the students with limited clinical experience had difficulty in creating an image of her psychosocial aspects. A lower achievement of imaging was also reported when paper patients were used [16].…”
Section: The Cue Acquisition Stagementioning
confidence: 88%
“…Previous studies have revealed that students tend to prefer video cases since they perceive video modality as authentic [16,17], interesting [18], motivating [19], and stimulating [20]. Video cases elicit students' attention and emotions [21], promote empathy [22], improve memory retention [17], increase understanding of the cases [18], and improve students' patient-centredness [23].…”
Section: Introductionmentioning
confidence: 99%
“… 27 The specificities of the parents’ lives are here considered important in demonstrating the ‘realness’ of the phenomenon and in motivating the students. Thus, while many video cases exclude the patient’s everyday life and its psychosocial aspects, focusing on medical interviews in the examination room only, 28 this video gives voice to the parent’s lifeworld 29 and opens the door visually to their homes and everyday activities.…”
Section: Methodsmentioning
confidence: 99%
“…Dagens studenter er vokst opp med visualisert informasjon og kommunikasjon, slik at kun tekstbaserte case og annet undervisningsmateriell kan derfor virke fremmed for studentene (Kędra & Žakevičiūtė, 2019). Tidligere studier har vist at case presentert gjennom video bidrar til at studentene oppfatter casene som mer autentiske (Ikegami et al, 2017), interessante og motiverende (Chan, 2010) sammenlignet med tekstbaserte case. Video kan bidra til økt forståelse av casene (Chan, 2010), men kan også påvirke studenters etiske og emosjonelle vurderinger sammenlignet med en skriftlig fremstilling (Nunohara et al, 2020;Yadav et al, 2011).…”
Section: Studentaktiv Laeringunclassified